Murine and Human Spermatids Are Characterized by Numerous, Newly Synthesized and Differentially Expressed Transcription Factors and Bromodomain-Containing Proteins. Issue 1 (1st July 2016) - Klaus, Elisabeth Sabine; Gonzalez, Nicola Helena; Bergmann, Martin; Bartkuhn, Marek; Weidner, Wolfgang; Kliesch, Sabine; Rathke, Christina
Abstract: Much of spermatid differentiation takes place in the absence of active transcription, but in the early phase, large amounts of mRNA are synthesized, translationally repressed, and stored. Most nucleosomal histones are then degraded, and chromatin is repackaged by protamines. For both transcription and the histone-to-protamine transition in differentiating spermatids, chromatin must be opened. This raises the question of whether two different processes exist. It is conceivable that for initiation of the histone-to-protamine transition, the already accessible, actively transcribed chromatin regions are utilized or vice versa. We analyzed the enrichment of different canonical TATA-box-binding, protein-associated factors and their variants in murine spermatids, diverse bromodomain-containing proteins, and components of the Polycomb repressive complexes PRC1 and PRC2 using quantitative PCR. We compared the enrichment of corresponding proteins in human and murine spermatids and analyzed the time frame of postmeiotic transcription and expression of histones, transition proteins, and protamines in human and murine spermatids using immunohistology. We correlated the expression of different transcription factors and bromodomain-containing proteins and the pattern of acetylated histones to active transcription and to the histone-to-protamine transition in both human and murine spermatids. Our findings suggest that differentiating spermatids use both common and specific features to open chromatin first for transcription and subsequently for histone-to-protamine transition.